Response of eight low-cost particle sensors and consumer devices to typical indoor emission events in a real home (ASHRAE 1756-RP). (7th February 2020) - Zou, Yangyang; Young, Matthew; Wickey, Morgan; May, Andrew; Clark, Jordan D.
Abstract : Many consumer-grade low-cost particle sensors have recently entered the market, potentially providing a means of inexpensively monitoring indoor air quality and eventually being used to control building systems. In this study, we evaluate several such products: three bare sensors (BS) and five integrated devices (ID) containing one or more of these sensors and additional features. We collocated the sensors with reference instruments in a real indoor environment for two and half months. During this time, we conducted 27 particle emission events of several different types (incense, candle, toast, spray, cooking, humidifier and open window). All ID and BS exhibited an ability to respond to different PM sources, although the magnitude of their responses varied. The ratio of the time-integrated signals and peaks of the sensor signals to the reference instruments during each event varied from close to zero to around approximately three. Similarly, correlations between one-minute low-cost sensor data and similar reference instrument data varied widely among the sensors and devices tested, with R 2 values between near zero and near one observed.